Leader-member-exchange and the workplace bully - Foster, Pamela J. (Kansas State University, 2012)
This dissertation investigated the relationship between a low-quality leader-member exchange (LMX) relationship and whether participants felt they were bullied at work. The study looked at retaliatory behavior as an outcome of experiencing bullying behavior. The study investigated whether ostracism would mediate the effect between LMX and workplace bullying and whether social support would moderate the relationship between workplace bullying and retaliatory behavior. The sample was comprised of 209 participants who were either employed by Kansas State University or were taking classes as non-traditional students at Kansas State University. The study sample was demographically 49.76% female and 50.24% male. The survey was administered using K-State’s on-line AXIO survey system, which ensured confidentiality and accurate data entry. The study found that a low-quality LMX relationship predicted workplace bullying and workplace bullying behavior predicted retaliatory behavior. Ostracism did not mediate the relationship between a low-quality LMX relationship and workplace bullying behavior, but social support did have moderating effects between workplace bullying behavior and retaliatory behavior. The moderated effects of social support showed a buffering effect for men with coworker support and an increase in retaliatory behavior for women for all forms of social support. The results are discussed in the context of understanding how organizational leadership can reduce the negative effects of workplace bullying behavior.
Keywords: Workplace bullying; Leader-Member Exchange LMX; Social support; Retaliation; Ostracism; Management (0454); Organizational Behavior (0703); Psychology (0621)